Beyond Light‐Trapping Benefits: The Effect of SiO2 Nanoparticles in Bifacial Semitransparent Ultrathin Cu(In, Ga)Se2 Solar Cells. Issue 11 (20th September 2022) - Li, Yong; Tabernig, Stefan W.; Yin, Guanchao; Polman, Albert; Schmid, Martina
Abstract : Bifacial semitransparent ultrathin Cu(In, Ga)Se2 solar cells (BSTUT CIGSe SCs) enable efficient usage of light and reduced raw material. By inserting the SiO2 nanoparticles (NPs) at the CIGSe/back–contact interface, this work optimizes the performance of BSTUT SCs under front and especially rear illumination, which has not been studied much so far. For the SCs with NPs, the short‐circuit current density increases by 4.1–4.4 mA cm −2 for front and by 6.4–7.4 mA cm −2 for rear illumination. In addition, a significantly improved fill factor for rear illumination highlights a benefit of the NPs beyond light trapping. A jet‐like focusing behind the NPs is observed, which in this case leads to a higher field localization near the pn junction, joint with an enhanced carrier generation and separation. Furthermore, a thinner In2 O3 :Sn (ITO) back contact is noticed to be favorable for effective light trapping, whereas thicker ITO is preferred for higher open‐circuit voltage. Overall, inserting NPs in BSTUT SCs is an effective and practical strategy to achieve a higher cost‐to‐efficiency ratio in photovoltaic device production. In our case, a maximum of 12.2% under front and 9.2% under rear illumination is achieved leading to a calculated bifacial efficiency of 15% for the ultrathin device. Abstract : SiO2 nanoparticles (NPs) inserted at the Cu(In, Ga)Se2 /In2O3 :Sn interface enhance the overall light absorption of bifacial semi‐transparent ultrathin solar cells. The NPs induce waveguide modes and enhance front and rear absorption in the ultrathin Cu(In, Ga)Se2 layer. The NPs also induce jet‐like forward scattering, which further increases the collection efficiency of photogenerated carriers under the rear illumination.